The Effectiveness of Group Guidance and Counseling with the Application of the Behavior Contract Technique in Improving Learning Motivation Among Students - Aprilianti, Eka (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This research aims to evaluate the effectiveness of group guidance and counseling using the behavior contract technique in increasing students' learning motivation. Through a quantitative approach and a pre-experimental research design with a one-group pretest-posttest design, The population in this study were all students in class XI, totaling 75 students at SMA Fathul Falah Bandar Mataram. The sample in this study consisted of students who showed low learning motivation, with a total of 8 people. A study on low learning motivation among eleventh-grade students at SMA Fathul Falah Bandar Mataram involves the entire eleventh-grade population, comprising a total of 75 students who meet the criteria for low learning motivation. From this population, a sample of 8 students was selected using the Non-Probability Sampling method and Purposive Sampling technique, which were determined based on attendance and recommendations from the head of student affairs. Data sources include the class attendance list during the research period, reports or recommendations from the head of student affairs, and the results of observing students' learning motivation using observation instruments or learning motivation questionnaires. Sample data includes students such as SSA, AAW, and DM, with details on gender, average scores, and specific learning motivation issues for each individual. In this research, the data analysis technique uses the Wilcoxon test, which measures the difference in pre-test and post-test means using a special formula. The sampling technique used was Non-Probability Sampling with the Purposive Sampling method, which is a sample selection technique based on certain considerations to obtain eight students who showed problems with low learning motivation. Research shows a significant increase in student learning motivation after receiving group counseling and guidance with behavioral contract techniques. Analysis of pre-test and post-test data using the Wilcoxon Test revealed significant changes, with an initial score of 181 and a final score of 336. The test results showed a Z value of 2,524 from the 11th-grade sample, confirming the effectiveness of group counseling and behavioral contracts in increasing students' learning motivation.